Is It Time to Supersede the Diagnostic Term “Melanoma In Situ with Regression?” A Narrative Review - Anna Colagrande; Giuseppe Ingravallo; Gerardo Cazzato (Dermatopathology, 2023)
Traditionally, the term melanoma in situ (MIS) is used to designate a horizontal (radial) growth phase of malignant melanoma (MM) in which there is no histological evidence of any invasion (or microinvasion) of neoplastic melanocytic cells into the superficial or papillary dermis. In daily dermatopathological practice, we are faced with misleading definitions, such as “melanoma in situ with regression,” which risk affecting homogeneity for comparison purposes of pathological reports of malignant melanoma. The authors conducted a literature review using PubMed and Web of Science (WoS) as the main databases and using the following keywords: “Malignant Melanoma in situ” or “Melanoma in situ” and “regression” and/or “radial growth phase regression.” A total of 213 articles from both analyzed databases were retrieved; finally, only eight articles in English were considered suitable for the chosen inclusion criteria. In consideration of the absence of studies with large case series, of reviews with meta-analyses, and, therefore, of a broad scientific consensus, expressions including “melanoma in situ with regression” should be avoided in the histopathological report. Instead, they should be replaced with clearer and more exhaustive definitions.